Overview of NCSRD Activation Experiments at JET - Vasilopoulou, T.; Savva, M. I.; Michelakaki, I.; Triantou, K.; Mergia, K.; Stamatelatos, I. E.; Messoloras, S.; Contributors, JET (HNPS Advances in Nuclear Physics, 2019)
The intense collaborative effort for electricity generation through fusion is currently focused on the exploitation of the Joint European Torus (JET) as well as on the preparation of its successors ITER and DEMO. Within this frame, several experiments are carried out at JET aiming to study crucial aspects related to the construction and operation of ITER as well as to the design of future fusion power plants.Most important, a high-performance Deuterium-Tritium campaign is expected to take place at JET in 2020 providing unique neutron yields up to 1.7×1021 neutrons. This paper focuses on the participation of NCSRD fusion technology group in JET nuclear analysis and, in particular, on the implementation of activation experiments at JET and discusses the main achievements in the light of their significance for optimizing future fusion activities and studies.